DETERMINAN DISIPLIN KERJA DOSEN : PENDEKATAN STRUCTURAL EQUATION MODELING DENGAN PROGRAM LISREL 8.8 - Qomusuddin, Ivan Fanani; Sam’un, Sam’un; Tamlekha, Tamlekha; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the influence of university leadership, organizational culture, and lecturer job satisfaction on work discipline. The research method uses a quantitative survey approach. The population of this study is lecturers of Private Islamic Religious Universities (PTKIS) in the West Java, and 107 lecturers were taken as a sample using random sampling techniques. The data collection technique is carried out by means of a questionnaire through google form media. The data analysis technique uses Structural Equation Modeling (SEM) with the help of IBM Statistical Package for Social Sciences (SPSS) Version 20 for Windows and Lisrel 8.8 software. The results of the SEM analysis prove that there is a positive and significant direct influence of university leadership on lecturer work discipline, lecturer job satisfaction on lecturer work discipline. However, there is no positive and significant influence of organizational culture on work discipline. This study recommends that universities optimize their leadership roles to improve lecturers' work discipline, considering the positive and significant influences found. In addition, it is necessary to develop strategies to strengthen lecturers' job satisfaction, because job satisfaction has also been proven to have a significant influence on discipline. On the contrary, since organizational culture does not have a significant influence, further evaluation of the elements of the organizational culture is required, to determine whether certain aspects of that culture need to be adapted or integrated with other approaches that are more effective in supporting the work discipline of lecturers